2021
DOI: 10.1021/acsomega.1c01702
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Chilli Leaf Curl Virus Using an Attenuated Total Reflection-Mediated Localized Surface-Plasmon-Resonance-Based Optical Platform

Abstract: The development of a nanoparticle-based optical platform has been presented as a biosensor for detecting targetspecific plant virus DNA. The binding dynamics of gold nanoparticles has been studied on the amine-functionalized surface by the attenuated total reflection (ATR)-based evanescent wave absorption method monitoring the localized surface plasmon resonance (LSPR). The developed surface was established as a refractive index sensor by monitoring the LSPR absorption peak of gold nanoparticles. This nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 102 publications
0
16
0
Order By: Relevance
“…The comparative screening of chili plants for begomoviral infection by PCR and AuNP assay demonstrated that the AuNP assay (77.7%) was better than the commonly used PCR methods (49.4%). More advanced detection methods have been performed using attenuated total reflection (ATR)-based evanescent wave absorption monitoring LSPR of AuNPs [ 54 ]. The binding dynamics of AuNPs has been studied on the amine-functionalized surface refractive index sensor and was developed by monitoring the LSPR absorption peak.…”
Section: Pathogen Biosensingmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparative screening of chili plants for begomoviral infection by PCR and AuNP assay demonstrated that the AuNP assay (77.7%) was better than the commonly used PCR methods (49.4%). More advanced detection methods have been performed using attenuated total reflection (ATR)-based evanescent wave absorption monitoring LSPR of AuNPs [ 54 ]. The binding dynamics of AuNPs has been studied on the amine-functionalized surface refractive index sensor and was developed by monitoring the LSPR absorption peak.…”
Section: Pathogen Biosensingmentioning
confidence: 99%
“…( a ) is before capturing the GLRaV-3 and ( b ) after binding of GLRaV-3 with antibody. The images are adopted from the references [ 54 , 36 ].…”
Section: Figurementioning
confidence: 99%
“…One such study reported the use of a Localized Surface-Plasmon-Resonance (LPSR) based optical platform for the detection of ChiLCV with a small volume (20–40 μL) of the sample. The LSPR absorbance signal could be monitored to detect the viral load and the sensitivity of LSPR assays by using aluminum nanoparticles for immobilization (Das et al, 2021 ).…”
Section: Diagnosticsmentioning
confidence: 99%
“…Recently RCA (Rolling Circle Ampli cation) and LAMP (Loop mediated isothermal ampli cation) assays have been established for rapid detection of begomoviruses [10], [11]. Recently Nano-particle-based optical platform has also been explored as a biosensor for detecting ChiLCV [12]. But these methods are only effective to investigate presence or absence of the virus.…”
Section: Introductionmentioning
confidence: 99%